Communication in disasters to support families with children with medical complexity and special healthcare needs: a rapid scoping review - Smith, Neale; Donaldson, Meghan; Mitton, Craig; Lee, Esther (Frontiers in Public Health, 2024)
Disasters can disrupt normal healthcare processes, with serious effects on children who depend upon regular access to the health care system. Children with medical complexity (CMC) are especially at risk. These children have chronic medical conditions, and may depend on medical technology, like feeding tubes. Without clear, evidence-based processes to connect with healthcare teams, families may struggle to access the services and supports they need during disasters. There is limited research about this topic, which has been pushed forward in importance as a result of the COVID-19 pandemic. The authors therefore conducted a rapid scoping review on this topic, with the intention to inform policy processes. Both the peer-reviewed and gray literatures on disaster, CMC, and communication were searched in summer 2020 and spring 2021. Twenty six relevant articles were identified, from which four main themes were extracted: 1. Cooperative and collaborative planning. 2. Proactive outreach, engagement, and response. 3. Use of existing social networks to connect with families. 4. Return to usual routines. Based on this review, good practices appear to involve including families, professionals, other stakeholders, and children themselves in pre-disaster planning; service providers using proactive outreach at the outset of a crisis event; working with existing peer and neighborhood networks for support; employing multiple and two-way communication channels, including social media, to connect with families; re-establishing care processes as soon as possible, which may include virtual connections; addressing mental health issues as well as physical functioning; and prioritizing the resumption of daily routines. Above all, a well-established and ongoing relationship among children, their caregivers, and healthcare teams could reduce disruptions when disaster strikes.